Water and surfaces as potential sources of pathogenic bacteria in Harare hospitals’ intensive care units - Dururu, Mathias; Muchesa, Petros; Chidzwondo, Farisai; Mangoyi, Rumbidzai (Journal of BioScience and Biotechnology, 2024)
Water and contaminated hospital surfaces have been reported as major causes of Hospital acquirеd (nosocomial) infections (HAIs), a significant global safety problem for both patients and medical staff. However, the frequency of Intensive Care Units (ICU)-HAIs has been reported to be at least 2-3 times greater in low- to middle-income countries, particularly in Zimbabwe, than in high-income countries. Thus, this study aimed at determining the presence of pathogenic bacteria in water and surfaces from selected high-risk areas within the intensive care units of three hospitals (A, B, and C) in Harare, Zimbabwe. Water and surface samples were collected and processed within 24 hours of collection. The water samples were tested for the presence of microbial indicators using standard methodology of microbial plating. The surface swabs were also investigated using microbial plating. The organisms that were found to be present in surface samples were then identified using biochemical tests and 16S polymerase chain reaction (16S PCR). The results showed no bacteria present in any of the water samples tested during the study. However, using morphological characteristics, six different types of bacteria were identified in surface samples. The bacteria identified to be present on surfaces were Escherichia coli, Salmonella, Shigella, Staphylococcus, Pseudomonas, and Streptococcus. Hospital A surfaces may be the major cause of some bacterial infection outbreaks, hence, there is a need for better ways of reducing contamination of surfaces in the intensive care units.